2021
DOI: 10.3390/biomedicines9030228
|View full text |Cite
|
Sign up to set email alerts
|

Oral Squamous Cell Carcinoma Is Associated with a Low Thrombosis Risk Due to Storage Pool Deficiency in Platelets

Abstract: Venous thrombo-embolism (VTE) disease is the second most common cause of mortality in cancer patients, and evaluation and prevention of thrombosis risk is essential. VTE-associated risk varies according to the type of tumor disease. Oral cancer is the most frequent type of head and neck cancer, and it represents approximately 2.1% of all cancers worldwide. Most tumors are squamous cell carcinomas and are mainly due to tobacco and alcohol abuse. VTE risk associated with oral squamous cell carcinoma (OSCC) is lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Authors found that, in vitro, OSCC cells induce platelet aggregation due to high TF activity; they confirmed this in vivo by detecting platelet aggregates and fibrin deposits in histological sections of primary mouse tongue tumors [62]. In orthotopic animal models, there was no significant difference in terms of blood cell counts or tail bleeding times between healthy and cancer-inoculated mice [62]. Using the same OSCC orthotopic mouse model, researchers studied platelet accumulation and fibrin generation in the cremasteric arteries after a laser induced injury.…”
Section: Oral Cancermentioning
confidence: 80%
See 3 more Smart Citations
“…Authors found that, in vitro, OSCC cells induce platelet aggregation due to high TF activity; they confirmed this in vivo by detecting platelet aggregates and fibrin deposits in histological sections of primary mouse tongue tumors [62]. In orthotopic animal models, there was no significant difference in terms of blood cell counts or tail bleeding times between healthy and cancer-inoculated mice [62]. Using the same OSCC orthotopic mouse model, researchers studied platelet accumulation and fibrin generation in the cremasteric arteries after a laser induced injury.…”
Section: Oral Cancermentioning
confidence: 80%
“…Despite the fact that HNC is between the 8th and 10th most common cancer in the world, there is surprisingly little information available about the risk of developing thrombotic events in this disease [60][61][62]. In a worrisome manner, the incidence of oral cavity and pharyngeal cancer is on the rise at a rate of 0.6% per year in the last decade alone [63].…”
Section: Oral Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, a potential mechanism that may explain this paradox was explained using a mouse model of tongue squamous cell carcinoma [ 26 ]. Surprisingly, platelet accumulation and fibrin generation in OSCC were highly inhibited in tumour-bearing mice versus healthy controls, suggesting a possible reduction in blood clot formation.…”
Section: Oscc and Thrombosis: A Paradoxical Relationship?mentioning
confidence: 99%